2019
DOI: 10.1109/access.2019.2946908
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Intensive Continuous Assessment With BeA in a Flipped Classroom Experience

Abstract: This paper presents the changes performed in a university course to adopt European Higher Education Area principles taking advantage of new technologies and educational approaches. Particularly, a Flipped Classroom model that also involves an Intensive Continuous Assessment approach is adopted, moving the presentation of theoretical contents to videos that can be watched outside of the classroom and using the classroom face-to-face time to provide explanations, problem solving and to perform assessment activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…Thus, many publications deal with Programming, since this is one of the most researched areas in CS education. We have found some examples of integrating FC with another teaching technique or methodology: Llamas-Nistal et al [43] observed improvements in student retention and passing rate when mixing FC with intensive assessment in a Computer Architecture course, and Chis et al [7] detected positive results in a CS1 course mixing FC with Problem Based Learning. On the contrary, Jonsson [21] measured low participation rates mixing FC and Just in Time Teaching in an Object-Oriented Programming course.…”
Section: The Use Of Flipped Classroom In Computer Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, many publications deal with Programming, since this is one of the most researched areas in CS education. We have found some examples of integrating FC with another teaching technique or methodology: Llamas-Nistal et al [43] observed improvements in student retention and passing rate when mixing FC with intensive assessment in a Computer Architecture course, and Chis et al [7] detected positive results in a CS1 course mixing FC with Problem Based Learning. On the contrary, Jonsson [21] measured low participation rates mixing FC and Just in Time Teaching in an Object-Oriented Programming course.…”
Section: The Use Of Flipped Classroom In Computer Sciencementioning
confidence: 99%
“…Finally, while most of the works mentioned within the scope of CS study full applications of the FC methodology, this work considers a partial application of it. The studies that observed positive results, either in learning outcomes [7], [14], [43], [45] or student's satisfaction [17], [46], mostly seem to deploy the FC approach on practical contents. Only Horton & Campbell's study [46] specifically focuses on an introductory topic about databases.…”
Section: A Increasing the Body Of Experiments About The Use Of Flippmentioning
confidence: 99%
“…However, their characteristics were often discernible from the overall research concept. Several studies (Jensen et al, 2018;Llamas-Nistal et al, 2019;Santos, 2021;Wang, 2017Wang, , 2019 adopted a predominantly postpositivist worldview, using experimental approaches and collecting quantitative data to support their hypotheses. Others (Arruabarrena et al, 2019;Mojtahedi et al, 2020;Moreno-Ruiz et al, 2019) were more inclined to a pragmatic worldview, often using mixed research methods to find solutions to practical problems.…”
Section: Research Approaches and Designsmentioning
confidence: 99%
“…However, almost every student chooses to follow the continuous assessment system, especially those who are taking the subject for the first time. [42].…”
Section: Experiments Description a Educational Contextmentioning
confidence: 99%